An Analysis of Educational Practices in Karnali Province through an Inclusive Education Perspective - Bhatta, Ravi Lal (Karnali Outlook: Knowledge Across Disciplines, 2026)
The objective of this study was to examine the effective management of educational processes from the perspective of inclusive education practices in Karnali Province, Nepal. The study used a convergent mixed-methods research design. The quantitative data was collected through online survey form from 25 academicians from teachers, University Lecturers, Administrators, and others, regardless of their affiliation with public or private educational institutions in Nepal and the qualitative information was collected from Random and purposive sampling techniques that were used to collect data from the respondents. Data and information were analyzed using quantitative and thematic technique, respectively. Inclusive schools have barriers and difficulties in managing teachers and students to attain curricular goals. Political influence, lack of training, retaining qualified and experienced teachers, lack of welcoming environment to all kinds of children with disabilities or without disabilities , managerial challenges related to leadership, teachers, students, pedagogic approach, technical, financial, administrative and health are critical for managing Inclusive schools and new opportunities have also began for head teachers’ capacity development, teachers’ professional development, use of new learning and teaching approach and pedagogical shift in teaching learning processes. There is a need for various pedagogic approaches and local community and government’ involvement to motivate students and develop inclusive schools. The study concludes that schools have difficulties in managing teachers and students to attain curricular goals. As the local governments have the constitutional and contextual roles to formulate educational policy and manage to suit the local context. They must be responsible for, and accountable to, managing, supervising, and supporting the schools in their jurisdictions.